2016
DOI: 10.1187/cbe.15-11-0230
|View full text |Cite
|
Sign up to set email alerts
|

Early Environmental Field Research Career Exploration: An Analysis of Impacts on Precollege Apprentices

Abstract: Longitudinal mixed-methods examination of two consecutive field-based environmental biology research apprenticeship programs for precollege youth indicates that the two-stage apprenticeship structure influenced social cognitive career variables necessary for persistence in pursuit of an environmental research career pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
(24 reference statements)
0
7
0
2
Order By: Relevance
“…The need to make the environmental workforce match the increasingly diverse demographics of human communities has prompted research inquiry on what factors specifically affect URM students' career choices in environmental science fields. For environmental careers, elements influencing URM engagement include many different factors such as family support (Armstrong et al 2007), participation in guided experiences in nature appreciation (whether in urban or more natural field sites; Aloisio et al 2018), exposure to careers in ecology (Morales et al 2020), connecting environmental study in some way to interests in solving local and global community problems that affect minorities (Bowser et al 2020), and field research experiences as high school or college students in any type of environmental setting (Flowers et al 2016, Burrow 2018, O'Connell et al 2018, Beltran et al 2020. All of these experiences can lead URM students into further study of the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to make the environmental workforce match the increasingly diverse demographics of human communities has prompted research inquiry on what factors specifically affect URM students' career choices in environmental science fields. For environmental careers, elements influencing URM engagement include many different factors such as family support (Armstrong et al 2007), participation in guided experiences in nature appreciation (whether in urban or more natural field sites; Aloisio et al 2018), exposure to careers in ecology (Morales et al 2020), connecting environmental study in some way to interests in solving local and global community problems that affect minorities (Bowser et al 2020), and field research experiences as high school or college students in any type of environmental setting (Flowers et al 2016, Burrow 2018, O'Connell et al 2018, Beltran et al 2020. All of these experiences can lead URM students into further study of the environment.…”
Section: Introductionmentioning
confidence: 99%
“… 2020 ), and field research experiences as high school or college students in any type of environmental setting (Flowers et al. 2016 , Burrow 2018 , O'Connell et al. 2018 , Beltran et al.…”
Section: Introductionmentioning
confidence: 99%
“…Flowers et al [23] presented a study examining two consecutive dual-staged career exploration apprenticeship models designed to convey real-world practices and connections to a research career. The initial model offered introductory field-skills training to the 10th and 11th-grade students to engage in scientific exploration at a nature reserve.…”
Section: Inquiry-driven Real-world Srepsmentioning
confidence: 99%
“…TERFers come to identify with scientists and find role models and friends to stay in contact with for support as they enter college. Both SIFT and TERF appear to influence decision making about college majors and open the door for these youth to pursue additional research experiences as they proceed on to college (Flowers et al ).
Before going into SIFT, I was unsure about what I wanted to study in college but after going through SIFT it showed me that I had more options than I thought I had.
…”
Section: What Happens For the Youth?mentioning
confidence: 99%